The Influence of Religious Education on the Religiosity of Roma Children in Slovakia. Issue 5 (19th October 2020) - Soltesova, Viktoria; Pleva, Matus
Abstract: The primary purpose of this research is the question of religiosity among secondary school-age Roma children attending Religious Education (RE) programs in Evangelical churches in Slovakia. This study adopted the questionnaire "Brief Multidimensional Measurement of Religiousness/Spirituality" used by the Fetzer Institute in a General Social Survey (GSS) to examine the religiosity of Roma children attending RE and not attending RE. We asked questions about their daily spiritual experiences and personal religious habits. This study revealed some variation in the values of both groups of respondents and the correlation coefficients describing the degree of relationship between them.